2018
DOI: 10.1021/acsami.8b14071
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Templated Synthesis of Lightweight, Elastic, and Conductive Nanotube Aerogels

Abstract: Conductive polymer (CP) nanotubes are fascinating nanostructures with high electrical conductivity, fast charge/discharge capability, and high mechanical strength. Despite these attractive physical properties, progress in the synthesis of CP nanotube hydrogels is still limited. Here, we report a facile and effective approach for the synthesis of polypyrrole (PPy) nanotube hydrogels by using the weakly interconnected network of self-assembled nanotubes of lithocholic acid as a soft template. The PPy nanotube hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Reproduced with permission. [105] Copyright 2018, American Chemical Society. c) without sodium cholate.…”
Section: Modification Of Polymer Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [105] Copyright 2018, American Chemical Society. c) without sodium cholate.…”
Section: Modification Of Polymer Materialsmentioning
confidence: 99%
“…Especially interesting is the possibility to form PPy nanotubes using lithocholic acid as a template. [ 105 ] The approach ( Figure ) developed by Liang et al is based on the self‐assembly properties of lithocholic acid, which formed tubular structures. Such tubular templates facilitated the synthesis of PPy nanotube hydrogels.…”
Section: Modification Of Polymer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Especially, the one-dimensional (1D) conducting polymerbased nanomaterials exhibit enhanced electron/mass transport capacity and stability compared to other nanostructured conducting polymers. 34,35 Recently, some researches have demonstrated that 1D conducting polymer-based nanomaterials are efficient ones for peroxidase mimicking, showing promising applications for biosensing and environmental monitoring. 36−39 thiophene) nanocables have been prepared from a wet chemical reaction between sodium tellurite and 3,4-ethylenedioxythiophene followed by a galvanic replacement process, which showed a superior peroxidase-like efficiency to sensitively detect H 2 O 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the last decades, conducting polymers such as polyaniline, polypyrrole, and polythiophene have been broadly applied in the areas of biosensing, catalysis, energy conversion and storage, and environmental technology due to their unique π-conjugated chain structures, low electrical resistance, rich surface functional groups, and favorable processibility. , Especially, the one-dimensional (1D) conducting polymer-based nanomaterials exhibit enhanced electron/mass transport capacity and stability compared to other nanostructured conducting polymers. , Recently, some researches have demonstrated that 1D conducting polymer-based nanomaterials are efficient ones for peroxidase mimicking, showing promising applications for biosensing and environmental monitoring. For example, Pd@poly­(3,4-ethylenedioxythiophene) nanocables have been prepared from a wet chemical reaction between sodium tellurite and 3,4-ethylenedioxythiophene followed by a galvanic replacement process, which showed a superior peroxidase-like efficiency to sensitively detect H 2 O 2 . On the other hand, 1D conducting polymers with a hollow nanostructure usually possess a high surface area and lower density, which is able to facilitate the electron and mass transport efficiency, showing great potential for enzyme mimicking .…”
Section: Introductionmentioning
confidence: 99%